Four Pole Limited Angle Toroidal Motor Magnetic Design - Akin Aydin; Ali Saygın (Gazi Üniversitesi Fen Bilimleri Dergisi)
This article presents the theoretical analysis of limited angle torque motors (LATM), numerical modeling for 4-pole types and the effect of various dimensions on motor performance. First, the magnetic equivalent circuit model and equations of the LATM are defined and the motor torque expression for 4 poles is established. Then AHP, a decision-making tool, is used as a reference to determine the best LATM design parameters. The cogging torque, constant torque region and peak torque value of the motor at the lower and upper values of the obtained design parameters are analyzed in the finite element analysis environment. The transient analysis of the best design considering certain limitations is performed and the operating performance is analyzed in no-load condition. With the proposed model, the torque of the 4-pole limited angle torque motor in the constant torque region is obtained at 95% of the peak torque. This value is verified by finite element analysis.